Synthesis of Nuclear and Chloroplast Data Combined With Network Analyses Supports the Polyploid Origin of the Apple Tribe and the Hybrid Origin of the Maleae—Gillenieae Clade - Hodel, Richard G. J.; Zimmer, Elizabeth A.; Liu, Bin-Bin; Wen, Jun (Frontiers in Plant Science, 2022)
Plant biologists have debated the evolutionary origin of the apple tribe (Maleae; Rosaceae) for over a century. The “wide-hybridization hypothesis” posits that the pome-bearing members of Maleae (base chromosome number x = 17) resulted from a hybridization and/or allopolyploid event between progenitors of other tribes in the subfamily Amygdaloideae with x = 8 and x = 9, respectively. An alternative “spiraeoid hypothesis” proposed that the x = 17 of Maleae arose via the genome doubling of x = 9 ancestors to x = 18, and subsequent aneuploidy resulting in x = 17. We use publicly available genomic data—448 nuclear genes and complete plastomes—from 27 species representing all major tribes within the Amygdaloideae to investigate evolutionary relationships within the subfamily containing the apple tribe. Specifically, we use network analyses and multi-labeled trees to test the competing wide-hybridization and spiraeoid hypotheses. Hybridization occurred between an ancestor of the tribe Spiraeeae (x = 9) and an ancestor of the clade Sorbarieae (x = 9) + Exochordeae (x = 8) + Kerrieae (x = 9), giving rise to the clade Gillenieae (x = 9) + Maleae (x = 17). The ancestor of the Maleae + Gillenieae arose via hybridization between distantly related tribes in the Amygdaloideae (i.e., supporting the wide hybridization hypothesis). However, some evidence supports an aspect of the spiraeoid hypothesis—the ancestors involved in the hybridization event were likely both x = 9, so genome doubling was followed by aneuploidy to result in x = 17 observed in Maleae. By synthesizing existing genomic data with novel analyses, we resolve the nearly century-old mystery regarding the origin of the apple tribe. Our results also indicate that nuclear gene tree-species tree conflict and/or cytonuclear conflict are pervasive at several other nodes in subfamily Amygdaloideae of Rosaceae.